Budidaya Tanaman Stevia Pemanis Alami Rendah Kalori Bersama Kader Kesehatan Desa Teguhan - Cahyaningtyas, Tiara Intan; Kusumawati, Naniek; Devi , Heidy Paramitha; Samsiyah, Nur; Lestari, Puput Tri; Anisa, Dinda Sir (Politeknik Negeri Cilacap, 2025)
The recent phenomenon is that on every inch of empty sidewalk, in front of shops, in front of schools, and on the side of the road there must be sellers of sweet drinks, especially jumbo tea. Excessive sweet drinks can increase the risk of diseases caused by excess sugar such as diabetes and obesity. The purpose of this community service activity (PkM) is to increase the knowledge of Teguhan Village health cadres regarding the dangers of obesity, diabetes, and the benefits of stevia. The community service methods used include counseling about the dangers of diabetes, obesity, stevia plant cultivation, and joint practice in planting and processing stevia plants until ready for consumption. This PKM activity resulted in an increase in knowledge among cadres by 63%. The percentage of knowledge before being given counseling regarding obesity, diabetes, and stevia was only an average of 28% and after the PKM activity ended, the average knowledge of cadres increased to 91%. These results are expected to reduce the use of cane sugar switch to stevia sugar and spread their knowledge to the surrounding community so that more people know about the benefits of stevia plants.